Toleransi dalam keberagaman: Upaya memperkuat persatuan bangsa di era modern - Taufiqah, Alya Nabila (Maliki Interdisciplinary Journal, 2026)
Indonesia is a country with a high level of diversity, including ethnicity, religion, culture, and language. This diversity is a national asset but also has the potential to cause conflict if not properly managed. Therefore, tolerance plays an important role in maintaining national unity in the modern era, which is characterized by rapid technological development and the widespread use of social media. This study aims to analyze the role of tolerance in diversity and efforts to strengthen national unity. The method used in this research is a literature study by reviewing relevant sources related to tolerance and diversity. The results show that tolerance has a strategic role in creating a harmonious society, preventing social conflicts, and strengthening solidarity and nationalism. However, there are several challenges, such as the spread of misinformation, hate speech, and increasing individualism. Therefore, efforts are needed through education, the role of family, strengthening Pancasila values, wise use of social media, and intercultural and interreligious dialogue. In conclusion, tolerance is a key factor in maintaining national unity and must be continuously fostered in society.